The Stock Market as a Central Hub of Macroeconomic Dynamics: Multivariate VAR Evidence on the Relationship between the Current Account and Indonesia’s Composite Stock Index (1990–2024) - Eka Desy Purnama (Dinasti Publisher, 2026)
This study examines how the stock market transmits global financial shocks to Indonesia’s current account. Using a multivariate VAR model with quarterly data (1990–2024), the analysis includes domestic variables current account, inflation, and interest rates—alongside global indicators (DJIA and WTI). Empirical results show that the lagged Indonesia Composite Stock Price Index (IHSG) is statistically significant in the current account equation. Granger causality tests indicate unidirectional causality from IHSG to the current account without reverse feedback. Impulse response analysis reveals immediate but transitory adjustments following stock market shocks. Forecast Error Variance Decomposition results indicate that IHSG explains approximately 5.4% of the medium-term forecast error variance of the current account, exceeding the contribution of other domestic macroeconomic variables. These findings provide quantitative evidence that IHSG operates as a central transmission channel within Indonesia’s macro-financial system.